Analisis Tingkat Kesulitan Guru Bimbingan Konseling dalam Memberikan Layanan BK di Sekolah Inklusif SMA Muhammadiyah Curup - Beni Azwar (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2023)
The study aims to examine the implementation of Counseling Guidance (BK) services in an inclusive school, namely SMA Muhammadiyah Curup. This research is motivated by the need for ABK so that they can develop more optimally like other ordinary students. While ABK has problems with; the process of adjustment at school, school stigma on ABK is considered to reduce school quality, lack of ABK learning facilities, bullying behavior on ABK, and labeling report cards that read inclusive students. For this reason, BK teachers must be able to provide complex and specific BK services that are easily understood and implemented by ABK and ordinary. These students can unite ABK and ordinary students in learning.The research method used a descriptive qualitative approach with descriptive analysis, namely analyzing the problems of counseling teachers at SMA Muhammadiyah Curup, using in-depth interviews and observations of counseling teachers and students. For technical data validity with source and technique triangulation, then the data is verified and displayed descriptively.The research results show that: First; BK services with a classical format can be applied to all students, Second; Counseling for children with mental retardation and mild autism requires special training on measurable changes in behavior, with reinforcement or rewards. Third; the consistency of school collaboration with parents is very necessary in order to maintain independent behavior that has been formed with empathy from all parties. Fourth; It is easier for BK teachers to make ABK independent with the same disorder than those with various disorders. Fifth; BK teachers don't understand sign language, Braille writing, and other unique things about ABK.